Is Fulminant Hepatic Failure the Nemesis for Liver Transplant Centers? A Two Decade Psychosocial and Long-Term Outcome Study. Issue 7 (July 2018) - Alsina, Angel; Alsina, Alexa; Athienitis, Alexia; Buggs, Jacentha; Aslam, Sadaf; Kemmer, Nyingi
Long-term outcomes in liver transplantation for acute liver failure (ALF) are poorly studied. The aim of the study was to identify psychosocial variables that affect adherence and late survival. Retrospective review of ALF liver transplant (LTx) patients between 1997 and 2017 (n = 47) was conducted. Psychosocial history, life stressors, and ability to participate in transplant were recorded. Survival was calculated using Kaplan-Meier and logistic regression. Eleven patients (31.5%) had poor adherence, four died, all from graft failure. Of 13 with fair and 12 with good adherence, two died, no adherence related. Poor adherence was associated with higher mortality (P = 0.04), but by Kaplan-Meier, their five- and 10-year survival was 78 and 54 per cent, versus fair and good adherence (five years, 83% P = 0.3). Participating in transplant decision improved survival (five years, 80%) versus not participating (five years, 61%; P = 0.03). Of 10 early deaths, three were neurologic and five of sepsis. Overall, one- and five-year survival was 78 and 69 per cent. ALF represents the nemesis of LTx programs. Psychosocial aspects pre-LTx, stressors, and poor adherence affected survival in this series. No improvement over two decades of ALF LTxs was observed. The ethics of transplanting these high-risk patients will be the subject of our future research.